(untitled) (Journal of Pharmaceutical Negative Results, 2023)
A Pharmaceutical Fungicide Or Fungistatic Used To Treat And Prevent Mycoses Such As Athlete's Foot, Ringworm, Candidiasis (Thrush), Serious Systemic Infections Such As Cryptococcal Meningitis, And Others Is Known as An Antifungal Medicine, Sometimes Known as An Antimycotic Medication. A Series Of 1,2,4 Triazole Analogs Have Been Designed Synthesized Characterized And Screened For A Wide Variety Of Therapeutically Interesting Drug Candidates Including Antifungal Agents, Anti-Inflammatory, Central Nervous System Stimulants, Antianxiety And Antimicrobial Agents. Among Screened Compound N-( (4-P-Toluidine Methyl) Piperazine -1-Yl ) Methyl )-4H-1,2, 4-Triazole -3-Amine Mono, Di Or Tri-Substituted Aniline Derivative Were Synthesized By Microwave Irradiation And Characterized By Proton Nuclear Magnetic Resonance (1H NMR), Infra-Red(IR), And Mass Spectroscopy (MS), And Biologically Screen For Antifungal Activity. The Novel Synthesized Derivative Triazole Show Antifungal Activity, Candida Albicans.